I think you meant to say "root" instead of "foot". Also, I think you meant to use the letter i instead of the number 1 on the left side of the equation. It should be this:
i = square root of -1 = sqrt(-1)
Often it's handier to use the shortcut "sqrt" for "square root"
Let's square both sides of the equation given:
i = sqrt(-1)
i^2 = (sqrt(-1))^2
i^2 = -1 ... notice squaring the square root have the two cancel out and go away
Now multiply both sides by i
i^2 = -1
i^2*i = -1*i
i^2*i^1 = -i
i^(2+1) = -i
i^3 = -i
which is the final answer